Morphometric Characterization of Nematode Parasites Infecting Periplaneta americana in Bulandshahr, Uttar Pradesh - Rani, Anjani (Journal for Research in Applied Sciences and Biotechnology, 2022)
This study investigates the morphometric characterization and distribution of nematode parasites infecting Periplaneta americana in Bulandshahr, Uttar Pradesh. The research aimed to identify the nematode species prevalent in various environments and analyze their impact on cockroach populations. Specimens of P. americana were collected from diverse sites, including sewage areas, urban kitchens, and garbage dumps, and examined for nematode infections. The study identified three primary nematode species—Rhabditis blumi, Heterorhabditis bacteriophora, and Steinernema carpocapsae—through microscopic and morphometric analyses. Statistical analysis revealed a significant correlation between environmental factors such as moisture and organic matter availability with nematode prevalence. The highest parasite load was found in sewage areas, where cockroaches exhibited behavioral changes and increased mortality. These findings suggest that parasitic nematodes play a crucial role in controlling P. americana populations, particularly in heavily contaminated environments. The study also highlights the potential use of entomopathogenic nematodes in integrated pest management strategies as an eco-friendly alternative to chemical pesticides. The research contributes to a better understanding of the ecological and biological significance of nematode parasitism in cockroaches and its implications for public health, emphasizing the need for sustainable pest control measures in urban environments.